Architectures : Meta-structures of Humanity, Morphic Strategies of Exposure. - International Architecture Exhibition Venetië 2004; Budak, Adam (Warsaw : Zacheta National Gallery of Art, 2004)
Lejman, Dominik ; Dominiczak, Jacek ; Oksiuta, Zbigniew ; nsMoonStudio ; Mayer H., Jürgen ; Hecker, Zvi ; Diller & Scofidio ; et al.
Polish Pavilion for La Fondazione Biennale di Venezia, 9th International Architecture Exhibition, Metamorph, Giardini di Castello, Venice, 12th September - 7th November 2004
kunstcatalogus